Multicultural Islamic Religious Education Learning to Build Religious Harmony - Rusli Takunas; Saepudin Mashuri; Jumri H. Tahang Basire; Gunawan B. Dulumina; Syahril; Siti Mughni Mohi (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
This research analyzes the Multicultural Islamic Religious Education Learning (MIREL) at SMKN 1 Poso in building religious harmony as a conflict resolution. Conflict socio-religious become a critical problem regarding diversity in schools and society. Meanwhile, Islamic religious education provided in schools does not prioritize a multicultural perspective, which includes the practices of different religions and other cultures. This study uses qualitative field research with a case study approach and data analysis, according to Miles and Huberman. Results show that this school carries out the MIREL formally-textual and informally-textual. Learning formally-textual is held through three stages. At the beginning stage, teachers contextualize the values of example and self-control through exemplary stories from the prophets. In the main stage, the teachers integrate the values of tolerance, harmony, democracy, unity, concern, and justice by presenting material that includes faith, morals, jurisprudence, and the history of Islamic culture. Teachers instill multicultural values of cooperation and responsibility in the closing stage by assigning group tasks. The school holds informally textual learning through the Religious Saturday program collaboration in cross-cultural, socio-religious, and humanitarian activities. This research has implications for strengthening the MIREL in schools to build sustainable religious harmony among students and society in the post-conflict area.